2014
DOI: 10.1371/journal.pone.0100777
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment with the Sodium Glucose Cotransporter 2 Inhibitor, Dapagliflozin, Ameliorates Glucose Homeostasis and Diabetic Nephropathy in db/db Mice

Abstract: Inhibition of sodium glucose cotransporter 2 (SGLT2) has been reported as a new therapeutic strategy for treating diabetes. However, the effect of SGLT2 inhibitors on the kidney is unknown. In addition, whether SGLT2 inhibitors have an anti-inflammatory or antioxidative stress effect is still unclear. In this study, to resolve these issues, we evaluated the effects of the SGLT2 inhibitor, dapagliflozin, using a mouse model of type 2 diabetes and cultured proximal tubular epithelial (mProx24) cells. Male db/db … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
191
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(211 citation statements)
references
References 30 publications
17
191
1
2
Order By: Relevance
“…S6 shows the time course of Me4FDG excretion into the urinary bladder with and without dapagliflozin (see also Movies S3 and S4). In general, dapagliflozin at this dosage inhibited Me4FDG uptake into pancreatic and prostate tumors by 40-50%, which compared well with the 50% reduction in the reabsorption of glucose from the glomerular filtrate (27). As in human tumors, Me4FDG uptake into in vitro slices of mouse tumors was blocked by dapagliflozin.…”
Section: Is Sglt Functional Activity Correlated With Sglt Expression supporting
confidence: 58%
See 2 more Smart Citations
“…S6 shows the time course of Me4FDG excretion into the urinary bladder with and without dapagliflozin (see also Movies S3 and S4). In general, dapagliflozin at this dosage inhibited Me4FDG uptake into pancreatic and prostate tumors by 40-50%, which compared well with the 50% reduction in the reabsorption of glucose from the glomerular filtrate (27). As in human tumors, Me4FDG uptake into in vitro slices of mouse tumors was blocked by dapagliflozin.…”
Section: Is Sglt Functional Activity Correlated With Sglt Expression supporting
confidence: 58%
“…In the dapagliflozin trial, the mice were subjected to microCT the day before the beginning of treatment and then weekly until the end of the trial; the efficacy of the treatment in blocking SGLT was confirmed by microPET/CT with Me4FDG in a subset of the animals involved in the study. The PET/CT scans allowed us to measure the excretion of Me4FDG into the urinary bladder as a positive control of drug efficacy; in the control mice, no Me4FDG was excreted into the bladder, whereas about 50% of the filtered glucose load was excreted in mice treated with the SGLT2 inhibitor (27). After the end of the trials, the mice were killed and the tumors were harvested for morphologic analysis, fixed in 4% paraformaldehyde in PBS (pH 7.4), and then sliced into 7-μm-thick slices on Superfrost microscope slides (Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and in vivo work has suggested that sodium glucose cotransport inhibition reduces markers of inflammation and fibrosis [18,19,[29][30][31]. Although we did not measure inflammatory markers in the present trials, future studies should assess the effect of SGLT2 inhibition on pro-inflammatory and pro-fibrotic mechanisms in diabetes and associated kidney disease.…”
Section: Discussionmentioning
confidence: 85%
“…This phenomenon is mostly explained by progression of β-cell apoptosis and dysfunction in the setting of diabetes, which is efficiently prevented by empagliflozin and other SGLT2i therapy [27,42,43]. SGLT2i therapy preserves β-cell integrity and functional capacity as shown by our immunohistological and -histochemical analysis.…”
Section: Discussionmentioning
confidence: 60%